New approaches to rationale pharmacotherapy of trigeminal neuralgia based on personalized medicine principles - V. V. Arkhipov; A. V. Sokolov; T. A. Rodina; D. L. Pozdnyakov; Е. А. Sокоvа (Регуляторные исследования и экспертиза лекарственных средств, 2018)
Optimization of pharmacotherapy (selection of optimal doses and dosing intervals) is a major objective of clinical pharmacology. This objective may be achieved, in part, by implementation of modern pharmacokinetic approaches and the use of therapeutic drug monitoring that consists in selection of an appropriate dose level and dosing interval based on information about drug concentrations at certain timepoints. This is particularly important for drugs with a narrow therapeutic range. The authors of the article advocate the usefulness of therapeutic drug monitoring in treating exacerbation of trigeminal neuralgia with carbamazepin and evaluate practical relevance of development of a new phenotyping method that could be used to increase pharmacotherapy efficiency and safety.